Reflexões sobre a apropriação de objetos na arte contemporânea - Littig, Sabrina Vieira (2015)
In this dissertation we discussed the movements around the appropriation issue evidencing the displacement of the ordinary object into the art field in three paradigmatic movements: Dadaism, Surrealism and the New Realism and its developments in contempor